Establishing and characterizing a new primary effusion lymphoma cell line harboring Kaposi’s sarcoma–associated herpesvirus - Osawa, Madori; Mine, Sohtaro; Ota, Shinichiro; Kato, Kengo; Sekizuka, Tsuyoshi; Kuroda, Makoto; Kataoka, Michiyo; Fukumoto, Hitomi; Sato, Yuko; Kanno, Takayuki; Hasegawa, Hideki; Ueda, Keiji; et al. (Infectious agents and cancer, 2016)
Primary effusion lymphoma is a rare distinct large B-cell neoplasm that is associated with Kaposi's sarcoma-associated herpesvirus (KSHV) infection. Over recent years, 9 KSHV-positive/Epstein-Barr virus (EBV)-negative PEL cell lines have been established. Tumor cells were collected from the pleural effusion of a 49-year-old male with AIDS. Cells were grown in RPMI1640 culture medium supplemented with 10 % fetus bovine serum. Single cell cloning was performed successfully by a limiting dilution method in a 96-well plate. The cell line obtained was designated SPEL. SPEL cells showed gourd-shaped morphology with a polarized nucleus, expressing CD38, CD138, and Blimp-1, but not B cell markers such as CD19 and CD20. Polymerase chain reaction analysis revealed that SPEL cells were positive for KSHV but negative for EBV. Tetradecanoylphorbol acetate induced expression of KSHV lytic proteins and the production of KSHV particles in SPEL cells. Subcutaneous inoculation of SPEL cells into severe combined immunodeficiency mice resulted in the formation of solid tumors. Next-generation sequencing revealed the 138 kbp genome sequence of KSHV in SPEL cells. Suberic bishydroxamate, a histone deacetylase inhibitor, induced the expression of KSHV-encoded lytic proteins and cell death in SPEL cells. A new KSHV-positive and EBV-negative PEL cell line, SPEL was established. This cell line may contribute to furthering our understanding of the pathogenesis of PEL and KSHV infection.